"ZnAlCrOx&HZSM-5" bifunctional catalyst for one-step alkylation of naphthalene and syngas. (15th January 2023) - Tang, Zhongqiang; Zhao, Siyuan; Zhao, Xiao; Jin, Runze; Wang, Jiaofei; Zhang, Zhuangzhuang; Hu, Haobin; Guo, Xinwen; Dai, Chengyi; Ma, Xiaoxun
Graphical abstract: Highlights: Process with syngas as alkylating reagent greatly improves reaction stability. The syngas route achieves an effective CO utilization rate of 29.87%. The tandem mode and spacing between different active sites are crucial. Migration of Zn is a main reason for the reduction of naphthalene conversion. Ce alleviates the migration phenomenon and effectively improves the catalyst life. Abstract: The conversion of naphthalene into high value-added intermediate, 2, 6-dimethylnaphthalene (2, 6-DMN), using methanol as an alkylating agent has been widely studied. However, the low conversion of naphthalene and the easy deactivation of catalysts due to carbon deposition still pose challenges for industrialization. This is attributed mainly to the huge difference in the conversion kinetics of naphthalene and methanol. Herein, we report the first one-step process for the synthesis of 2, 6-DMN from naphthalene by direct alkylation with syngas over "ZnAlCrOx&HZSM-5″ bifunctional catalyst. Compared to the traditional alkylation process of naphthalene with methanol, the direct alkylation of naphthalene with syngas not only shortened the process route and improved the reaction balance of syngas to methanol, but also improved the effective utilization rate of CO (29.87 %), naphthalene conversion, and catalyst stability. Results indicated that the alkylation of naphthalene could be improved by appropriately narrowing the spacing between the ZnAlCrOx oxide and HZSM-5. The acid strength and acidity on the external surface of HZSM-5 were modified by P or Si to improve the initial conversion of naphthalene and the selectivity for 2, 6-DMN. The difficulty in determining the deactivation point of catalysts with multiple active sites under complex catalytic systems was solved by adopting a strategy of "improve shortcomings". The decline of metal activity in this reaction was found to be the main reason for catalyst deactivation. Doping of Ce into ZnAlCrOx helped to improve the stability of the catalyst from 80 h to 120 h.